Femtosecond dynamics of correlated many-body states in C60 fullerenes. (29th November 2016) - Usenko, Sergey; Schüler, Michael; Azima, Armin; Jakob, Markus; Lazzarino, Leslie L; Pavlyukh, Yaroslav; Przystawik, Andreas; Drescher, Markus; Laarmann, Tim; Berakdar, Jamal
Abstract: Fullerene complexes may play a key role in the design of future molecular electronics and nanostructured devices with potential applications in light harvesting using organic solar cells. Charge and energy flow in these systems is mediated by many-body effects. We studied the structure and dynamics of laser-induced multi-electron excitations in isolated C60 by two-photon photoionization as a function of excitation wavelength using a tunable fs UV laser and developed a corresponding theoretical framework on the basis of ab initio calculations. The measured resonance line width gives direct information on the excited state lifetime. From the spectral deconvolution we derive a lower limit for purely electronic relaxation on the order of τ el = 10 − 3 + 5 fs. Energy dissipation towards nuclear degrees of freedom is studied with time-resolved techniques. The evaluation of the nonlinear autocorrelation trace gives a characteristic time constant of τ vib = 400 ± 100 fs for the exponential decay. In line with the experiment, the observed transient dynamics is explained theoretically by nonadiabatic (vibronic) couplings involving the correlated electronic, the nuclear degrees of freedom (accounting for the Herzberg–Teller coupling), and their interplay.